The viral hypothesis in multiple sclerosis: role of Epstein-Barr virus and human endogenous retroviruses - Morandi, Elena (2017)
Epstein Barr Virus (EBV) is a major risk factor in Multiple Sclerosis (MS), via as yet unclear mechanisms. Several hypotheses have been proposed to explain how EBV infection could cause MS and the aim of this thesis was to better understand the mechanisms of action of EBV in the context of MS studying a) the role of EBV in myelin antigen presentation by B cells and b) the association of HERVs with MS.